Kedudukan Notaris Sebagai Saksi di Persidangan Kaitannya Dengan Hak Ingkar Atas Tanggung Jawab Notaris Dalam Menjaga Kerahasiaan Akta Otentik - Karina Raiza Abubakar (Faculty of Law Universitas Islam Indonesia, 2024)
The problem of proving a deed with the right to deny concerning the notary's responsibility to maintain the confidentiality of the deed has several conflicts. The purpose of this study is to determine the position of a notary as a witness in court in relation to the right to deny the notary's responsibility to maintain the confidentiality of an authentic deed when asked to be a witness in court. This study is a normative study, with a statute approach. The primary legal materials consist of laws and regulations such as the Civil Code, HIR, and the Notary Law. The secondary legal materials used consist of literature and legal journals. The results of this study show that in civil cases, written evidence is the main evidence. Still, the request for a notary to be a witness in reading the deed cannot be done because it is contrary to the notary's obligation to maintain the confidentiality of the deed. The existence of the right to deny makes the notary entitled to refuse to give testimony in court. However, in its implementation there is a conflict of interest between the deed as evidence and the notary's responsibility, this is caused by Articles 54 and 66 making the regulations in the Notary Law contradictory to other laws. Thus, it is important to then be able to reconsider and further study in depth the provisions on the responsibilities and obligations of notaries in the Notary Law with other contradictory regulations.Keywords: Right to Refuse, Evidence, Notary's Responsibility AbstrakPermasalahan pembuktian akta dengan hak ingkar kaitannya dengan tanggung jawab notaris untuk menjaga kerahasiaan akta mengalami beberapa benturan. Tujuan dari kajian ini adalah untuk mengetahui bagaimana kedudukan notaris sebagai saksi di persidangan kaitannya dengan hak ingkar atas tanggung jawab notaris dalam menjaga kerahasiaan akta otentik, ketika diminta untuk menjadi saksi di persidangan, Kajian ini merupakan penelitian normatif, dengan pendekatan perundang-undangan (statute approach). Adapun bahan hukum primer yang digunakan terdiri dari peraturan perundang-undangan sepertti Kitab Undang-Undang Hukum Perdata, HIR, dan Undang-Undang Jabatan Notaris. Bahan hukum sekunder yang digunakan terdiri dari literatur serta jurnal-jurnal hukum. Hasil dari kajian ini diketahui bahwa dalam perkara perdata bukti tulisan merupakan barang bukti utam, namun permohonan notaris sebagai saksi dalam pembacaan akta tersebut tidak dapat dilakukan karena bertentangan dengan kewajiban notaris dalam menjaga kerahasiaan akta dan adanya hak ingkar membuat notaris berhak menolak memberikan kesaksian dipersidangan. Namun implementasinya terdapat benturan kepentingan antara akta sebagai barang bukti dengan tanggung jawab notaris hal ini disebabkan oleh Pasal 54 dan 66 membuat peraturan dalam Undang-Undang Jabatan Notaris menjadi kontradiktif dengan undang-undang lainnya. Sehingga, menjadi suatu hal yang penting untuk kemudian dapat mempertimbangkan kembali serta mengkaji lebih lanjut secara mendalam terkait ketentuan tanggung jawab dan kewajiban notaris dalam Undang-Undang Jabatan Notaris dengan peraturan-peraturan lainnya yang kontradiktif.Kata kunci: Hak Ingkar, Pembuktian, Tanggung Jawab Notaris